Photocatalytic Degradation of Synthetic Sulfur Pollutants in Petroleum Fractions under Different pH and Photocatalyst - Hamdan, Mohamad Alif Hakimi; Hairom, Nur Hanis Hayati; Zaiton, Nurhafisza; Harun, Zawati; Soon, Chin Fhong; Hubadillah, Siti Khadijah; Jamalludin, Mohd Riduan; Che Jusoh, Nurfatehah Wahyuny; Abdul Jalil, Aishah (Emerging Advances in Integrated Technology, 2021)
Thiophene is one of the sulfur compounds in the petroleum fraction that can be harmful to living things and lead to a critical effect on the ecosystem. Photocatalytic degradation is one of the promising methods in treating wastewater as it can mineralization of pollutants into carbon dioxide and water. Other than that, this method is non-toxic and relatively low cost. The production of hydroxyl radicals playing a vital role in the degradation of organic pollutants. It has been claimed that the usage of zinc oxide (ZnO) nanoparticles could give an excellent degradation process as this photocatalyst have high photosensitivity, low cost and chemically stable. However, the preparation method of ZnO nanoparticles will affect the agglomeration, particle size, shape and morphology of particles and lead to influence the photocatalytic activity in degrading thiophene. Therefore, this study focused on the effectiveness of ZnO nanoparticles in the presence of fibrous nanosilica (KCC-1) and polyethylene glycol (PEG) as the capping agent to degrade synthetic thiophene. ZnO/KCC-1 had been synthesized via the precipitation method and characterized by using Fourier Transform Infrared (FTIR). The chemical bond and nature of the photocatalyst from the FTIR results proved that the synthesis process to produce the ZnO/KCC-1 was succeed. The large surface area of KCC-1 increases the effectiveness of ZnO which is supported by the experimental data. Accordingly, the optimum condition for photocatalytic degradation of thiophene is under pH 7 by using ZnO/KCC-1 as photocatalyst. Hence, it is believed that this research could be implemented to remove the thiophene in petroleum fraction from the actual industrial effluents and this can preserve nature in the future.